Factors Affecting Food Waste Behavior (Case Study Of Surakarta City Community) - Wahyu Adhi Saputro; Aris Prio Agus Santoso (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
Recent global issues are always related to food waste. Indonesia is also recorded to have an index value that is in the serious category. Conditions that are quite happening in fact are also followed by high numbers or values ​​of food waste in Indonesia. It is recorded that food waste in Indonesia reaches 300 kilograms of food waste per person every year. The flow of food waste is usually sourced in urban areas caused by many, one of which is the city of Surakarta. This study aims to determine the factors that influence the behavior of food waste in the city of Surakarta. This study used a sample of 30 people from the city of Surakarta. The data analysis method used in this research is multiple regression analysis. Based on the results of the study, it can be seen that simultaneously the independent variables consisting of income level, frequency of eating, education level, gender and number of household members affect the level of food waste. Partially there are only two variables that affect food waste, namely education level and frequency of eating, while the remaining three variables, namely education level, gender and number of household members have no effect on food waste.